Effect of solar variability on transionospheric radio wave propagation in the equatorial region - Bhattacharyya, A.; Engavale, B.; Tiwari, D.; Bose, S. (My University, 2006)
Growth of plasma instabilities in the post-sunset equatorial ionospheric F region gives rise to irregularities known by the generic name: equatorial spread F (ESF), which scatter incident VHF or higher frequency radio waves to produce scintillations on trans-ionospheric radio waves. Changes in large scale (> 10 km) electron density distribution in the equatorial and low latitude ionosphere due to electrodynamic effects associated with magnetic storms, influence the generation of ESF irregularities as seen in the pattern of occurrence of nighttime equatorial scintillations that may be specifically linked with magnetic activity. Besides such effects due to transient solar events, it is well known that the probability of occurrence of ionospheric scintillations caused by ESF irregularities as well as the strength of these scintillations during different phases of the solar cycle show a significant modulation of the generation and evolution of these irregularities by solar cycle related changes in the ionosphere and thermosphere. Evolution of spatial structure in the ESF irregularities determines the spatial scales that occur in the ground scintillation pattern during different phases of a scintillation event, and these spatial scales together with the dynamics of the irregularities determine the extent of degradation of transionospheric radio signals. Solar cycle effects on the structure and dynamics of ESF irregularities and hence on degradation of transionospheic radio signals during magnetically quiet periods, as also the effect of magnetic activity on the generation of ESF irregularities are discussed here on the basis of long term spaced receiver scintillation observations at an equatorial location.
Keywords: Equatorial plasma bubbles; Ionospheric scintillations; Magnetic activity; Solar variability; Equatorial region; Radio wave